The correlations between structure, rheology, and cell growth in peptide-based multicomponent hydrogels - Du, Eric Y; Ziaee Farzaneh; Wang, Liyuan; Nordon, Robert E; Thordarson Pall (Polymer journal, 2020)
Factorial analysis of the interactions between three hydrogel-forming peptides based on three different biological motifs, namely, fibronectin: Fmoc-GFFRGD, collagen: Fmoc-GFFGER, and laminin: Fmoc-DDIKVAV, was conducted through rheology and live cell imaging using L929 fibroblasts. Gels were formed from each of these three peptide gelators alone and in various combinations. Cellular growth was tracked for the first 48 h in time-lapse movies by counting fluorescent nuclei and segmenting the cell area. The correlation between cell growth and the gel structure was characterized by linear regression analysis. While all peptide combinations showed good biocompatibility, the single-component Fmoc-DDIKVAV gel had the most positive effect on cell growth, while Fmoc-GFFRGD was the least biocompatible and had the lowest growth rate and cell area. Linear regression modeling demonstrated possible negative and positive interactions between Fmoc-GFFRGD*Fmoc-DDIKVAV and Fmoc-GFFRGD*Fmoc-GFFGER, respectively. No correlation was observed between gel stiffness and cellular growth. However, an increase in the strain crossover point for the elastic and loss moduli was associated with greater cell proliferation. This may indicate that elastic gels that store the work of cell deformation during cytokinesis are required for proliferation.Multicomponent hydrogel systems were formed using combinations of three self-assembled peptide based gelators with motifs inspired by fibronectin, collagen, and laminin, respectively. After a systematic study on the how the properties of hydrogels correlate with cell growth and proliferation, it was found that cell growth was significantly impacted by the hydrogels’ resistance to strain which was defined by their crossover point. This indicates that the ability of the gel to efficiently store the work of deformation during cell division is the most important factor for cellular proliferation.